2020
DOI: 10.1055/a-1069-7698
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Outcome of Congenital Corrected Transposition of the Great Arteries – A Multicenter Report of 69 Cases

Abstract: Objective Congenital corrected transposition of the great arteries (ccTGA) is a rare congenital cardiac anomaly which remains difficult to diagnose prenatally. We aim to investigate the natural history, associated anomalies and the outcome of patients in prenatally diagnosed ccTGA. Method This was an international multicenter retrospective analysis of fetuses with a diagnosis of ccTGA from 2002 to 2017. We reviewed clinical and echocardiographic databases of seven centers. Anatomic survey and fetal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…Due to the rarity of ccTGA, we still know little about the spectrum and the outcome of prenatally diagnosed cases. There are case reports and few retrospective series with a small number of patients similar to our study, one larger study of 98 cases published in 2019 [8] and a series of 69 cases in 2020 [9]. Sharland et al reported on a series of 34 cases focusing on prenatal diagnosis.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Due to the rarity of ccTGA, we still know little about the spectrum and the outcome of prenatally diagnosed cases. There are case reports and few retrospective series with a small number of patients similar to our study, one larger study of 98 cases published in 2019 [8] and a series of 69 cases in 2020 [9]. Sharland et al reported on a series of 34 cases focusing on prenatal diagnosis.…”
Section: Discussionsupporting
confidence: 84%
“…Day et al presented the largest cohort of prenatally diagnosed patients with discordant atrioventricular and ventriculoarterial connections including a postnatal median follow-up of 9.5 years [8]. In their multicenter report, Vorisek et al included 69 fetuses with ccTGA, focusing on the prenatal sonographic features and the confirmation postnatally while there were few information regarding the outcome and follow-up time was short (30 days) [9]. Our study comprises data from 37 prenatally diagnosed fetuses with detailed information regarding time of diagnosis, intrauterine course, maternal characteristics, additional cardiac and extracardiac malformations and a mid-term follow-up (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations